Clonal or not clonal? Investigating hospital outbreaks of KPC-producing Klebsiella pneumoniae with whole-genome sequencing. (July 2017) - Ruppé, E.; Olearo, F.; Pires, D.; Baud, D.; Renzi, G.; Cherkaoui, A.; Goldenberger, D.; Huttner, A.; François, P.; Harbarth, S.; Schrenzel, J.
Abstract: Objectives: Whole-genome sequencing (WGS) is a promising tool for identifying transmission pathways in outbreaks caused by multidrug-resistant bacteria. However, it is uncertain how the data produced by WGS can be best integrated into epidemiologic investigations. Methods: We tested various genomic analyses to identify clonal groups in two distinct outbreaks of Klebsiella pneumoniae carbapenemase–producing K. pneumoniae that occurred in Switzerland in 2013 and 2015. In blinded fashion, we sequenced 12 strains involved in the two outbreaks, respectively, and six that were epidemiologically unrelated. We analysed genomic commonalities from conserved genes to plasmid-borne antibiotic resistance genes (ARGs) and contrasted these results with available epidemiologic evidence. Results: Using WGS, blinded analysts correctly identified the two clusters of strains from the two outbreaks. Nonetheless, the 2015 index strain was found to be slightly different (1–3 single nucleotide variants) from the strains recovered from secondary cases, likely because prior long-term carriage (3 years) by the index patient allowed for genetic mutations over time. Also, we observed occasional loss of ARG-bearing plasmidic fragments in outbreak-causing strains. Conclusions: Retrospective WGS analysis was successful in identifying clonal groups in both outbreaks. Still, data should be analysed with caution in cases of previous long-term carriage of the studied bacteria.